Answer:
-32
Step-by-step explanation:
-4 + f(8) + 3 x g(-7) = ?
To find f(8), look at each of the f(x) function and find x = 8. The y value is the answer you will plug in for f(8). The same goes for g(-7), but you will be looking at the g(x) function at x = -7.
f(8) = -4
g(-7) = -8
Make sure you solve in the correct order using PEMDAS.
-4 + (-4) + 3 x (-8) = -32
4x + 6 < -6
- 6 -6
4x < -6
— —
4 4
x < -1.5
I'm sorry but I'm not into square roots yet :(
Answer:
1. 0=0
2. 0=17
Step-by-step explanation:
The answer is a all of the points